IMPROVING STUDENT’S CRITICAL THINKING SKILLS THROUGH SETS VISION LEARNING - Hairida, Hairida; Hadi, Lukman (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
This research was raised under low skills of critical thinking of Senior High School (SHS) students. The purpose of this research was to unveil the effectiveness of SETS vision for critical thinking. This research was a quasi experiment with non equivalent control group design. The sampling of this research used purposive sampling.Class XI MIA1 as experiment class get SETS vision treatment, while XI MIA2 got conventional learning model. The main instrument of this research was critical thinking skills portrayed from 12 test items which have been validated and highly reliable. The testing of hypothesis using t-test concluded that there was a difference of critical thinking in experimental class students to control class students. The average ability of critical thinking in experimental class was higher than the control class. Thus, it can be concluded that SETS can improve students critical thinking.